Answer:
X = 21/4 - 7/4 = 14/4 = 7/2 = 3 and 1/2
Step-by-step explanation:
X + (2 and 1/2) - 3/4 = 5 and 1/4
X + 2 and 2/4 - 3/4 = 5 and 1/4 <--- common denominator
X + 10/4 - 3/4 = 21/4
X + 7/4 = 21/4
X = 21/4 - 7/4 = 14/4 = 7/2 = 3 and 1/2
Answer:
D
Step-by-step explanation:
3 (4x + 18y) means that 3 will multiply 4x and 18y factor which results to 12x + 54y
hence dissimilar to the original expression
Answer:
k(x) + g(x) = x² - 3x + 4
General Formulas and Concepts:
<u>Alg I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 3x - 7
g(x) = 2x² - 3x + 1
h(x) = 4x + 1
k(x) = -x² + 3
<u>Step 2: Find k(x) + g(x)</u>
- Substitute: k(x) + g(x) = -x² + 3 + 2x² - 3x + 1
- Combine like terms (x²): k(x) + g(x) = x² + 3 - 3x + 1
- Combine like terms (Z): k(x) + g(x) = x² - 3x + 4
It’s C’ D’ hope this helps
I think you mean
sqrt x + 5 = sqrt (x+45)
if you plug in x = 4,
left side = sqrt 4 + 5 = 2+ 5 = 7
right side = sqrt (4+45) = sqrt 49 = 7
so the answer is x = 4 :)